2023
DOI: 10.1186/s12905-023-02300-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of client satisfaction with family planning service among family planning users in Ethiopia: a systematic review and meta-analysis

Abstract: Background Considering the importance of client satisfaction in the quality of family planning services, a regular evaluation should be carried out. Several studies have been conducted in Ethiopia, but so far there were no pooled estimates of the prevalence of customer satisfaction with family planning services in the country. Therefore, this systematic review and meta-analysis was intended to estimate the pooled prevalence of client satisfaction with Ethiopian family planning services in Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The satisfaction of clients in sexual and reproductive health (SRH) services serves as a pivotal indicator, gauging the level of contentment a client derives from the services provided by healthcare professionals. Consequently, it mirrors the disparity between the anticipated service and the experience, as perceived by the client [ 6 ]. The satisfaction of clients is an essential component of quality and hence is expected to improve through better compliance with the service, at the same time, satisfied clients will generate demand in the community and assist in the recruitment of new clients who can use the services [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The satisfaction of clients in sexual and reproductive health (SRH) services serves as a pivotal indicator, gauging the level of contentment a client derives from the services provided by healthcare professionals. Consequently, it mirrors the disparity between the anticipated service and the experience, as perceived by the client [ 6 ]. The satisfaction of clients is an essential component of quality and hence is expected to improve through better compliance with the service, at the same time, satisfied clients will generate demand in the community and assist in the recruitment of new clients who can use the services [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the meta-analysis that, clients’ satisfaction with family planning services in Ethiopia was 56.78% [ 6 ]. Despite high client satisfaction with FP services, the 2016 Ethiopian Demographic and Health Survey (EDHS) reported that over a third of women had stopped using FP within a year [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation